Feeding Habits of Bigeye Tuna (Thunnus obesus) in the Western Indian Ocean Reveal a Size-Related Shift in Its Fine-Scale Piscivorous Diet - Lin, Chien-Hsiang; Lin, Jing-Siang; Chen, Kuo-Shu; Chen, Meng-Hsien; Chen, Chiee-Young; Chang, Chih-Wei (Frontiers in Marine Science, 2020)
This study analyzed the piscivorous diet of bigeye tuna (Thunnus obesus) through species identification of both fish and otolith remains in stomachs of 183 bigeye tuna collected in the western Indian Ocean. A total of 642 fish remains and 1021 fish otoliths were examined. Prey items identified in the fish and otolith remains were not completely consistent. Although 12 items out of the 53 identified taxa were found in both remains, 20 items of fish remains were not found in otolith remains, and 21 items were added only from the otoliths. The main fish remains were Alepisauridae, which accounted for 13.9%. Most of the otoliths belonged to Myctophidae (49.5%) and Scopelarchidae (21.4%). Three prey items, namely Valenciennellus tripunctulatus, Evermannella sp., and Zenion sp., were recorded for the first time in the diet of bigeye tuna from the region. The otolith remains substantially enhanced the taxonomic resolution of the diet. Bigeye tuna stomach contents were independent of location, depth, and time of catch but varied with tuna size. The proportion of dominant Myctophidae prey items decreased markedly as the tuna size increased, whereas the proportion of Macrouridae increased with size. In addition, larger bigeye tuna were found feeding on larger prey (Electrona risso and Scopelarchus analis), demonstrating that diet changes in both prey composition and size are related to the ontogeny of the fish.